Triathlon for Beginners : Everything You Need to Know About Training, Nutrition, Kit, Motivation, Racing, and Much More - Golding, Dan (Triathlon Hacks Dan Golding, 2012)
Are you thinking about getting into triathlon or doing your first race? Have you finished a couple of races and are keen to improve your time? Do you find the whole sport daunting and confusing? Are you a little intimidated by everybody else who looks like they know what they are doing? This easy to understand and insightful book is packed with practical ways you can improve and it will help you